An intergenic non-coding rRNA correlated with expression of the rRNA and frequency of an rRNA single nucleotide polymorphism in lung cancer cells. - Yih-Horng Shiao; Sorin T Lupascu; Yuhan D Gu; Wojciech Kasprzak; Christopher J Hwang; Janet R Fields; Robert M Leighty; Octavio Quiñones; Bruce A Shapiro; W Gregory Alvord; Lucy M Anderson (PLoS ONE)
Background Ribosomal RNA (rRNA) is a central regulator of cell growth and may control cancer development. A cis noncoding rRNA (nc-rRNA) upstream from the 45S rRNA transcription start site has recently been implicated in control of rRNA transcription in mouse fibroblasts. We investigated whether a similar nc-rRNA might be expressed in human cancer epithelial cells, and related to any genomic characteristics. Methodology/principal findings Using quantitative rRNA measurement, we demonstrated that a nc-rRNA is transcribed in human lung epithelial and lung cancer cells, starting from approximately -1000 nucleotides upstream of the rRNA transcription start site (+1) and extending at least to +203. This nc-rRNA was significantly more abundant in the majority of lung cancer cell lines, relative to a nontransformed lung epithelial cell line. Its abundance correlated negatively with total 45S rRNA in 12 of 13 cell lines (P = 0.014). During sequence analysis from -388 to +306, we observed diverse, frequent intercopy single nucleotide polymorphisms (SNPs) in rRNA, with a frequency greater than predicted by chance at 12 sites. A SNP at +139 (U/C) in the 5' leader sequence varied among the cell lines and correlated negatively with level of the nc-rRNA (P = 0.014). Modelling of the secondary structure of the rRNA 5'-leader sequence indicated a small increase in structural stability due to the +139 U/C SNP and a minor shift in local configuration occurrences. Conclusions/significance The results demonstrate occurrence of a sense nc-rRNA in human lung epithelial and cancer cells, and imply a role in regulation of the rRNA gene, which may be affected by a +139 SNP in the 5' leader sequence of the primary rRNA transcript.